2021
DOI: 10.1038/s41598-021-84730-8
|View full text |Cite
|
Sign up to set email alerts
|

Blast-induced temporal alterations in blood–brain barrier properties in a rodent model

Abstract: The consequences of blast-induced traumatic brain injury (bTBI) on the blood–brain barrier (BBB) and components of the neurovascular unit are an area of active research. In this study we assessed the time course of BBB integrity in anesthetized rats exposed to a single blast overpressure of 130 kPa (18.9 PSI). BBB permeability was measured in vivo via intravital microscopy by imaging extravasation of fluorescently labeled tracers (40 kDa and 70 kDa molecular weight) through the pial microvasculature into brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 95 publications
(138 reference statements)
0
33
0
Order By: Relevance
“…Increased levels of brain MMP-9, MMP-9 mRNA, and plasma MMP-9 have been observed acutely after a 130-kPa blast exposure in association with blood–brain barrier dysfunction [ 66 ]. Gelatin zymography of purified cerebral vascular fractions showed that levels of MMP-2 and MMP-9 could also be increased at 6 weeks post-blast exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Increased levels of brain MMP-9, MMP-9 mRNA, and plasma MMP-9 have been observed acutely after a 130-kPa blast exposure in association with blood–brain barrier dysfunction [ 66 ]. Gelatin zymography of purified cerebral vascular fractions showed that levels of MMP-2 and MMP-9 could also be increased at 6 weeks post-blast exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because gliovascular and neurovascular interactions control cerebral blood flow at multiple levels, their disruption following blast exposure would be expected to affect cerebral autoregulation. Morphological, biochemical and functional studies of humans and animal models have identified the vasculature as a primary target for blast-induced tissue damage [ 2 , 6 , 32 , 38 41 , 45 , 50 , 54 , 63 , 66 , 75 , 82 , 112 114 , 116 , 130 133 , 138 ]. Considerable evidence supports the concept of a thoracic effect whereby pressure waves transmitted through the systemic circulation damage the brain providing an additional mechanism for why blood vessels and perivascular cellular elements may be particularly susceptible to blast injury [ 116 , 117 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations